POST-PANDEMIC MSME BUSINESS STRATEGY: DIGITAL MARKETING INNOVATION AND TRANSFORMATION - Grace Citra Dewi; Yulianah Yulianah; Deny Bernardus; Bambang Sugiyono Agus Purwono; Chicilia Nova Yatna (SEAN Institute, 2023)
Today, small and micro-sized firms, also known as MSMEs, are one of the types of companies that provide essential assistance to the economic endeavors of the local community. The expansion of micro, small, and medium-sized enterprises demonstrates that this industry continues to play an important role in the economy of the community. Nevertheless, the COVID 19 Pandemic has had a significant effect on this industry. MSME actors need to develop a variety of business strategies and then transform those strategies into activities that involve digital marketing if they want their businesses to survive and thrive. As a result, the objective of this study is to conduct an analysis of the business strategy that will be utilized by MSMEs following the conclusion of the pandemic, with a focus on digital marketing and internet marketing. This investigation takes a qualitative approach and makes use of descriptive research tools. The findings of the study indicate that developing a digital business strategy can be an alternative survival strategy for MSMEs during the current Covid19 pandemic. This can be accomplished through digital and online marketing as well as the development of innovation through the improvement of product quality and improvements in product attributes. It is hoped that this modification to the strategy will allow the company to increase its market share and keep its turnover steady during the pandemic, while at the same time being able to adapt to the changes that are occurring in the business environment as a result of the digital age.